Volume of Air Gaps under Clothing and Its Related Thermal Effects (Journal of Fiber Bioengineering and Informatics, 2018)
Influenced by clothing style and fit, as well as human body contour, the distribution of air gaps entrappedbetween human body skin and inner surface of clothing is complex and difficult to measure. The three-dimensional body scanning technology provides a realistic method to quantify the air gap volume byscanning the surface image of human body and clothing. This research measures the air gap volumeof thirty experimental clothing using a 3D body scanner and analyzes the effect of clothing size andmechanical property of fabric on air gap volume under clothing. The experimental clothing is made ofdifferent fabrics with increasing chest circumference from 92 cm to 108 cm. To investigate the relationshipbetween air gap volume and thermal property of clothing, a thermal manikin is used to measure thethermal insulations of experimental clothing. As the air gap volume increases with the garment size, thethermal insulations of clothing do not linearly increase. The thermal insulation begins to decrease whenthe chest circumference of experimental garments becomes more than 100 cm due to the onset of naturalconvection. This research is helpful to study the affecting factors of air gap volume under clothing andestimate the effect of air gap volume on the thermal property of clothing.